Organoid Models in Cancer Immunotherapy: Bioengineering Approach for Personalized Treatment - Syarifah Tiara Noorintan; Chelsie Angelius; Fuad Gandhi Torizal (Immuno)
Recent advances in organoid technology have revolutionized cancer biology and therapeutic interventions, offering personalized immunotherapy treatment. Organoids, three-dimensional cell cultures derived from patient tumors, accurately replicate the tumor microenvironment, providing unprecedented insights into tumor-immune interactions and therapeutic responses. In this literature-based study, we discuss various culture methods for the diverse applications of organoids in cancer immunotherapy, including drug screening, personalized treatment strategies, and mechanistic studies. Additionally, we address the technological challenges associated with these methods and propose potential future solutions to accelerate the development of novel immunotherapeutic approaches. This review highlights the transformative potential of organoid models in advancing preclinical cancer immunotherapy modeling, screening, and evaluation, paving the way for more effective and personalized cancer treatments.